Static spherically symmetric solutions in general projective relativity - Singh T.; Singh G.P. (My University, 2025)
Static spherically symmetric solutions have been obtained for general projective relativity with n=0 and n≠0 both in isotropic and curvature coordinates. In curvature coordinates, only a restricted exact solution is possible. However, an approximate solution can always be obtained following a method similar to Vanden Bergh. In these spacetimes there is no horizon, but only a naked singularity at r=0. Thus there are no black holes. It is shown that there is no solution in static, spherically symmetric, conformally flat spacetime. © 1990 Plenum Publishing Corporation.